Review Artikel: Pengaruh Variasi Bahan Aktif terhadap Nilai SPF pada Sediaan Sunscreen - Najma Kamila Zahra; Rosalba Sirly Najia; Cindy Fitria Dwi Nova; Yomanda Yomanda; Camelia Azka (Journal of Educational Innovation and Public Health, 2026)
Indonesia, as a tropical country, is exposed to high levels of ultraviolet (UV) radiation, increasing the risk of skin damage. Sunscreen is widely used as a protective measure indicated by the Sun Protection Factor (SPF) value. This study aimed to evaluate the effect of active ingredient variations on SPF values and other influencing factors. A literature review with a descriptive-comparative approach was conducted using research articles published between 2021 and 2026 from Google Scholar, PubMed, ScienceDirect, and Elsevier. A total of seven eligible articles were analyzed. The results showed that the type of active ingredients, concentration, combination of ingredients, and dosage form significantly influence SPF values. Natural ingredients generally produce low to moderate SPF values, while combinations of active ingredients result in significantly higher SPF due to synergistic effects. Increasing the concentration of active ingredients also leads to higher SPF values. Additionally, dosage forms such as creams, serums, sunscreen powder and foundations affect sunscreen effectiveness through their film-forming ability on the skin. In conclusion, the combination of active ingredients and higher concentrations provides more optimal protection against UV radiation.